MOTIVASI BELAJAR MAHASISWA PRODIPENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU PADA PEMBELAJARANCHOUKAI1 - Daffa Afanin; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research aims to understand the motivation to study of the year first college students in FKIP department of Japanese Language of Riau University on the subject of Choukai 1. This research used descriptive method with a quantitative approach. The respondents on this research was 38 of the year first student college students in FKIP department of Japanese Language of Riau University. The result suggests that the motivation to study Choukai is considerably high which is based on the also considerably high score percentage of 78.2%. In this research it is known that the motivation to study is divided by two categories which are innate study motivations, and acquired study motivations. the percentage of intrinsic learning motivation scores was 78.64% and the percentage of extrinsic learning motivation scores was 77.6%.Key Words:Motivation, Learning Motivation Choukai